(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The preservation and transmission of moral and ethical values through oral literature remain a foundational pillar of national identity and youth socialization. This qualitative academic investigation analyzes the profound educational and upbringing ideas embedded within traditional Karakalpak folk epics (dastans). Utilizing historical-pedagogical and psychological analytical frameworks, the study examines canonical texts such as "Alpamys," "Edige," and the uniquely Karakalpak epic "Kyrk Kyz" (Forty Girls) to isolate their core pedagogical mechanisms. The research identifies how these epics historically functioned as comprehensive, narrative-driven educational systems designed to instill patriotism, psychological resilience, ethical integrity, and civic duty within the younger generation. Notably, the qualitative review highlights the progressive, gender-inclusive pedagogical models presented in "Kyrk Kyz," which feature female protagonists exhibiting exceptional intellectual and leadership agency. The findings confirm that Karakalpak folk epics transcend mere literary aestheticism; they operate as sophisticated ethnopedagogical tools that provide active cognitive and behavioral scaffolding. Systematically integrating these traditional educational concepts into modern instructional curricula is identified as a strategic necessity to fortify the moral architecture and psychological stability of contemporary youth in a rapidly globalizing educational environment.